Ecotheology Education in Indonesian High School based on Quranic Perspective and University Courses - Budi Prakoso, Satrio (LECTURES: Journal of Islamic and Education Studies, 2025)
The Quran of Islam, contains verses that address environmental concerns and well-being. Some verses, underscore the significance of environmental awareness and the necessity of preserving the natural world for the benefit of all living beings. The science and religion education program facilitates special emphasis on issues related to water resources. The objective of this study was to suggest water resources in environmental education and programs in Indonesian schools, with a view to cultivating environmental awareness. This result demonstrated that any interpretation (tafsir) of Al Furqan both verse 48 and 49 exhibited keywords pertaining to rainwater, cleansing, and human awareness. The syllabus and objectives of each course at the three universities offering programs in environmental engineering have been outlined. The development of environmental education lessons and programs in each high school subject is integrated with the interpretation of Al Furqan and university courses. The current study proposes lessons and educational programs, which balance theory in the classroom and practice outside the classroom, with the aim of fostering eco-theological education, with a special emphasis on developing awareness of water resources. The programs encompassed four subjects pertaining to water resources, drawing upon the guidebook, learning module and curriculum of natural science and religion study in high school.